2019
DOI: 10.1111/jgs.16081
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Treatment in US Long‐Term Nursing Home Residents With and Without Dementia

Abstract: OBJECTIVES To describe patterns of antihypertensive medication treatment in hypertensive nursing home (NH) residents with and without dementia and determine the association between antihypertensive treatment and outcomes important to individuals with dementia. DESIGN Observational cohort study. SETTING All US NHs. PARTICIPANTS Long‐term NH residents treated for hypertension in the second quarter of 2013, with and without moderate or severe cognitive impairment, as defined by the NH Minimum Data Set (MDS) Cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Another national study of NH residents also found that poor prognosis factors (cognitive impairment and functional impairment) were associated with potential overtreatment for HTN in residents with dementia. 47 This is consistent with the geriatric palliative Fig. 3.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Another national study of NH residents also found that poor prognosis factors (cognitive impairment and functional impairment) were associated with potential overtreatment for HTN in residents with dementia. 47 This is consistent with the geriatric palliative Fig. 3.…”
Section: Discussionsupporting
confidence: 86%
“…NH residents with LLE/AD may be at lower risk of fall or fracture, given institutional monitoring and dependence in ADL; however, an opportunity to improve fall prevention via less intensive treatment remains for mobile residents. Documentation of LP was not strongly associated with antihypertensive deprescribing; other studies showed mixed associations, where this factor was strongly associated with less intensive antihypertensive treatment 47 but not with deprescribing. 10 Again, lack of associations between these factors and deprescribing can stem from the unclear clinical recommendations in this population.…”
Section: Discussionmentioning
confidence: 65%
“…There are currently several pieces of evidence that recommend less intensive control in people with multimorbidity, especially in cases of dementia or limited life expectancy [ 25 ]. In general, blood pressure lower than 140/90 mmHg has been associated with a higher risk of falls and even mortality [ 8 , 26 , 27 ]. In our study we have proposed measures for pharmacological adjustment in people whose mean systolic blood pressure (SBP) was under 130 mmHg in the last year.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension (HT) and Cardiovascular Therapy: There is currently evidence suggesting less intensive monitoring in people with multimorbidity, particularly in cases of dementia or limited life expectancy [ 38 ]. Globally, blood pressure under 140/90 mmHg has been associated with a higher risk of falls and mortality [ 39 , 40 , 41 ]. We considered an antihypertensive medication as an IP in EOL patients when the patient’s mean systolic blood pressure has been lower than 130 mmHg over the last year [ 31 ].…”
Section: Methodsmentioning
confidence: 99%